Perlindungan Hukum bagi Perempuan Korban Patriarki dalam Warisan Adat Batak Toba Berdasarkan CEDAW : Penelitian - Yolanda, Ria Selvia (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This study discusses legal protection for Batak Toba women subjected to patriarchal inheritance practices. The patrilineal system places men as the sole heirs, while women—especially daughters and widows—receive only limited rights before marriage. This practice contradicts the principle of equality guaranteed by the 1945 Constitution and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), ratified through Law No. 7 of 1984. The study aims to analyze the legal consequences of inheritance-based gender discrimination and identify forms of fair legal protection for women. A normative juridical approach is employed through literature review and field interviews. Findings reveal that discriminatory inheritance practices risk triggering agrarian conflicts and economic marginalization. Implementation of legal protection at the local level remains weak due to dominant customary norms and low public legal awareness. Therefore, harmonization between customary, national, and international law, along with community education, is needed to ensure gender justice and effective legal protection for Batak Toba women.